Analytic Hierarchy Process (AHP) dan Fuzzy TOPSIS pada Pemilihan Himpunan Pairing Terpilih dari Jadwal Penerbangan - Dinita Rahmalia; Awawin Mustana Rohmah; Nuril Lutvi Azizah (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2020)
In the flight industry, there are two highest costs such as fuel cost and crew cost. The crew cost is affected by pairings selected from flight schedule. This research will explain about selecting the set of selected pairings using Analytic Hierarchy Process (AHP) and Fuzzy Technique for Order Performance by Similarity to Ideal Solution (Fuzzy TOPSIS). Before using either Fuzzy AHP or Fuzzy TOPSIS, it will be formed collection of the set of selected pairings using greedy algorithm. After collection of the set of selected pairings is formed, then we determine goal and criteria. The goal is selecting the set of selected pairings from some alternatives. For each the set of selected pairings, there are some criterions such as the number of deadhead, the number of pairing A2, the number of pairing A3, the number of pairing A4, the number of pairing A5, and the number of pairing A6. Based on simulation results, both AHP and Fuzzy TOPSIS can select and give the rank of priority in entire the set of selected pairings. Pada industri maskapai penerbangan, terdapat dua biaya yang sangat besar yaitu biaya bahan bakar dan biaya kru. Biaya kru dipengaruhi oleh pairing yang terpilih dari jadwal penerbangan. Pada penelitian ini akan dilakukan pemilihan himpunan pairing terpilih menggunakan metode Analytic Hierarchy Process (AHP) dan Fuzzy Technique for Order Performance by Similarity to Ideal Solution (Fuzzy TOPSIS). Sebelum menggunakan AHP atau Fuzzy TOPSIS, akan dibentuk kumpulan dari himpunan pairing terpilih menggunakan greedy algorithm. Setelah kumpulan himpunan pairing terpilih terbentuk, maka dibentuk goal dan kriteria. Goal adalah memilih himpunan pairing terpilih dari beberapa alternative. Pada setiap himpunan pairing yang terpilih, terdapat beberapa kriteria seperti jumlah deadhead, jumlah pairing A2, jumlah pairing A3, jumlah pairing A4, jumlah pairing A5, dan jumlah pairing A6. Berdasarkan hasil perhitungan, metode AHP dan Fuzzy TOPSIS dapat memilih dan memberi peringkat prioritas pada pemilihan himpunan pairing terpilih.